The Fear of God and the Classification of Science: Abraham bar Ḥiyya (d. ca. 1140) and the Andalusi Reception of Al-Fārābī’s Enumeration of the Sciences (Iḥṣāʾ al-ʿulūm) - González Diéguez, Guadalupe (Théologiques)

(untitled) (Institut d’études religieuses de l’Université de Montréal, 2021)
This article traces the association between wisdom and the fear of God in two encyclopedias of science that circulated in medieval Iberia: Enumeration of the Sciences by al-Fārābī and The Foundations of Intelligence and the Tower of Faith by Bar Ḥiyya. It offers insight into the polemical reception of al-Fārābī's work in the Iberian Peninsula; an analysis of Bar Ḥiyya's introduction to his encyclopedia, in which the fear of God occupies a central place; and an analysis of the epilogue of the only Andalusian manuscript that preserves al-Fārābī’s Enumeration, which also emphasizes the fear of God. The article argues that al-Fārābī's rather scandalous reputation in al-Andalus could explain the framing of his classification of the sciences, and those inspired by it, with pious considerations on the fear of God as a necessary condition to the study of science.